MANAJEMEN SABAR MOTIVASI SUKSES DALAM KEHIDUPAN - Sutarman, Sutarman (AL-MISBAH (Jurnal Islamic Studies), 2014)
In modern era, there are many problems of life that be received by human beings. God in the Holly Qur?an ask to the human being, in order to get success in life  ?must be patient. ? It has relationship in every time and unlimited that must belongs to someone. Many problems of life which complexs, it is need approach how to manage it. Problems above, as like problem of economics, problem of social, problem  of politics, problem of culture, and problem of jobless, etc. As the human being, they must have resilience attitude to solve the probems. If someone is rich and has much money it is better for doing something well, as like for building the school, mosque, and helping someone which need. But if someone is poor and has no much money it is better be patient, work hard and always remember God in every where, everytime and do praying. There fore, they  will get the better life, and will get success.